Synthetic nanoscale electrostatic particles as growth factor carriers for cartilage repair. Issue 3 (18th November 2016) - Shah, Nisarg J.; Geiger, Brett C.; Quadir, Mohiuddin A.; Hyder, Nasim; Krishnan, Yamini; Grodzinsky, Alan J.; Hammond, Paula T.
Abstract: The efficient transport of biological therapeutic materials to target tissues within the body is critical to their efficacy. In cartilage tissue, the lack of blood vessels prevents the entry of systemically administered drugs at therapeutic levels. Within the articulating joint complex, the dense and highly charged extracellular matrix (ECM) hinders the transport of locally administered therapeutic molecules. Consequently, cartilage injury is difficult to treat and frequently results in debilitating osteoarthritis. Here we show a generalizable approach in which the electrostatic assembly of synthetic polypeptides and a protein, insulin‐like growth factor‐1 (IGF‐1), can be used as an early interventional therapy to treat injury to the cartilage. We demonstrated that poly(glutamic acid) and poly(arginine) associated with the IGF‐1 via electrostatic interactions, forming a net charged nanoscale polyelectrolyte complex (nanoplex). We observed that the nanoplex diffused into cartilage plugs in vitro and stimulated ECM production. In vivo, we monitored the transport, retention and therapeutic efficacy of the nanoplex in an established rat model of cartilage injury. A single therapeutic dose, when administered within 48 hr of the injury, conferred protection against cartilage degradation and controlled interleukin‐1 mediated inflammation. IGF‐1 contained in the nanoplex was detected in the joint space for up to 4 weeks following administration and retained bioactivity. The results indicate the potential of this approach as an early intervention therapy following joint injury to delay or even entirely prevent the onset of osteoarthritis. Abstract : Nanoscale polyelectrolyte complexes diffuse through cartilage tissue and deliver growth factor for cartilage repair.